Validation of a LC-UV method for determination of tildipirosin in goat milk - Galecio, JS; Hernandis, V; Escudero, E; Marín, P (Journal of the Hellenic Veterinary Medical Society, 2023)
A simple, rapid, low-cost, and sensitive high-performance liquid chromatographic method was developed to determine tildipirosin in milk goat. Milk samples were precipitated with acetonitrile, and after evaporation, tildipirosin was determined by reverse-phase chromatography with an ultraviolet detector set at a wavelength of 289 nm. Tildipirosin was separated on a Zorbax Eclipse XDB-C18 column, 150 x 3.0 mm, 5 μm with gradient chromatographic elution. The retention times for tildipirosin and tylosin tartrate were 4.4 min and 10.5 min, respectively. Calibration curves were ranged from 100 to 2500 µg/L. The lower limit of detection was 75 µg/L, and the lower limit of quantitation was 100 µg/L. The accuracy and precision were always <15% except for LOQ < 20%. Mean recovery was 95.6 %. This procedure can be applied to perform pharmacokinetic studies in lactating animals and be useful to detect residues in dairy products.